Medicinal plants in burns treatment – a systematic review - Łopuszyńska, Inga; Adamowicz, Dominik; Rudziński, Patryk; Wosińska, Alicja; Meliksetian, Astrik; Pazik, Dorota; Kosecka, Katarzyna; Cieślik, Aleksandra; Jargieło, Anna; Kosieradzka, Karolina (Journal of Education, Health and Sport, 2023)
Introduction and aim. The World Health Organization (WHO) reports that around 11 million people experience burn injuries each year.1,2 Burn injuries occur when tissue damage is caused by various factors such as UV radiation, heat, chemicals, or electric current.3,4 While burns primarily affect the skin, they can also extend to deeper tissues like bones or muscles. When the skin is burned, its vital functions, including protection against the external environment, pathogens, and evaporation, are compromised.1 The appropriate treatment method must be chosen based on the burn stage, the patient's condition, and the cause. The aim of this paper is to provide a comprehensive review based on literature, concerning superficial burns and sunburns treatment, with a focus on nature-derived topical treatment methods. Material and methods. PubMed database was searched for the following terms: “burns”, “burn treatment”, “aloe vera”, “sunburn”, “centella asiatica”, “climate change”, “wound healing” for the articles published between 2005-2023 and written in the English language. Conclusion. Herbal-derived compounds, with their diverse mechanisms of action, antibacterial activity, and safety profiles present a competitive alternative to conventional treatment of burns and sunburns, however, there are still not enough clinical trials to assess the effectiveness and safety profiles of nature-derived compounds.